Mapping and design as interrelated processes : constructing space-time narratives (2019)
I present a short processual account (Kitchin et al. 2013) of three re-cartographies of one and the same region, south-west Flanders, which touches upon some contemporary issues that cut across the disciplines of cartography and urbanism. The three re-cartographies re-imagine the territory of south-west Flanders in contemporary terms. Produced within the context of urbanism, they adopt a designerly approach to research by cartography, implying an orientation towards (re)shaping the environment. The re-cartographies are purposefully contextual. They aim to rediscover and reactivate the potentials inherent within the site, while at the same time attempting to formulate a (partial) response to contemporary spatial problematics. Critical re-mapping is a way to expand the spatial imagination, and in this sense augments the capacity of designers and stakeholders to engage constructively with the environment. Re-cartography is a partly accumulative and partly iterative urbanist practice, one that oscillates between re-inscribing and re-constructing, between re-imagining and engaging with the territory; simultaneously practising the territory and the map as-a-process.